Respuesta :

Explanation:

Let's solve this problem graphically. Here we have the following equation:

[tex]sin^{-1}(4x) + sin^{-1}(3x) = -\frac{\pi}{2}[/tex]

So we can rewrite this as:

[tex]f(x)=sin^{-1}(4x) + sin^{-1}(3x) \\ \\ g(x)= -\frac{\pi}{2}[/tex]

So the solution to the equation is the x-value at which the functions f and g intersect. In other words:

[tex]f(x)=g(x) \\ \\ sin^{-1}(4x) + sin^{-1}(3x) = -\frac{\pi}{2}[/tex]

Using graphing calculator, we get that this value occurs at:

[tex]\boxed{x=-0.2}[/tex]

Ver imagen danielmaduroh
ACCESS MORE